DEVELOPMENT OF ELECTRO -TRAWL SYSTEM IN MARINE ENVIRONMENT. - NAMBOODIRI, K SREEDHARAN; VIJAYAN, V (Fishery Technology, 2017)
High voltage pulsed current produced on board a trawler is fed to electrodes distributed along the foot rope of a trawl net through 2 core TRS cable which builds up a homogeneous electrical field around the net mouth. By comparative fishing tests with the electrified and non-electrified 32 m. long wing trawl net, the increase in total catch of shrimps and fishes was found to be 19.8 and 36%, respectively.